A randomised double-blind controlled study of Deep Brain Stimulation for dystonia in STN or GPi – A long term follow-up after up to 15 years. (March 2022) - Hock, Aske Nicolai; Jensen, Steen Rusborg; Svaerke, Katrine Wordenskjold; Brennum, Jannick; Jespersen, Bo; Bergdal, Ove; Karlsborg, Merete; Hjermind, Lena Elisabeth; Lokkegaard, Annemette
Abstract: Aim: This is a long-term open follow-up of a prospective double-blind crossover study, where electrodes were bilaterally implanted in both the Subthalamic nucleus (STN) and internal pallidum (GPi) in patients with isolated dystonia. Methods: Patients with isolated dystonia were included to undergo surgery with Deep Brain stimulation (DBS) and after randomization, in a double-blind cross-over study, receiving bilateral stimulation of either STN or GPi for 6 months in each target. Preoperative and postoperative assessments with the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) and the 36-item Short Form Health Survey (SF-36) were performed. In this long-term follow-up (LFU), these ratings were repeated, and patients were evaluated with cognitive tests. Results: 21 patients were included in the protocol, 9 patients with generalized dystonia, 12 with a diagnosis of cervical dystonia. The mean duration of disease was 19.3 years, age at time of surgery 50.1 years. Fourteen patients participated in the LFU. At a mean follow-up of 10.2 years (range 4.8–15.4), BFMDRS movement score was improved with a mean of 36% (p < 0.05) compared with baseline. At LFU both a statistically significant improvement of stimulation in STN on BFMDRS movement score (p = 0.029) and Gpi (p = 0.008) was demonstrated, no significant difference was found between the two targets (p = 0.076). SF-36 improved for both targets. Conclusion: In this study we performed a long-term follow-up in 14 patients with cervical or generalized dystonia, who received stimulation in GPi, STN or both. The mean follow-up time was more than 10 years. Our data support a long-term effect of both STN-DBS and GPi-DBS in dystonia with equal effect and safety for up to 15 years. STN has been proven a viable safe and effective target and may be used as an alternative to GPi in both adult-onset cervical dystonia and generalized dystonia. Highlights: Deep brain stimulation is an efficient and safe treatment for dystonia with effect for up to 15 years. There is equal long-term effect when using GPi or STN as target of stimulation. DBS do not cause cognitive decline in dystonia in STN or GPi after long term treatment.